Highly cross-linked polyether-based 1, 2, 3-triazolium ion conducting membranes with enhanced gas separation properties. (November 2016) - Zhou, Xu; Obadia, Mona M.; Venna, Surendar R.; Roth, Elliot A.; Serghei, Anatoli; Luebke, David R.; Myers, Christina; Chang, Zhengmian; Enick, Robert; Drockenmuller, Eric; Nulwala, Hunaid B.
Graphical Abstract: Highlights: A monotopic approach yields cross-linked 1, 2, 3-triazolium-based membranes. Huisgen 1, 3-dipolar azide-alkyne cycloaddition and N -alkylation are combined. Free-standing membranes with T g  ∼ −60 °C, T d5  ∼ 230 °C, E ′ ∼ 4 MPa are obtained. Anhydrous ionic conductivities >10 −6  S/cm at 30 °C are reached. Membranes show CO2 permeabilities of 59–110 Barrer and CO2 /N2 selectivity of 25–48. Abstract: A series of cross-linked polyether-based 1, 2, 3-triazolium ion conducting membranes are prepared via the combination of thermally promoted Huisgen 1, 3-dipolar cycloaddition of a dialkyne and a diazide poly(trimethylene ether glycol) monomers with in-situ N -alkylation of the resulting poly(1, 2, 3-triazole)s with varying contents of 1, 10-diiododecane as cross-linking agent. The resulting free-standing membranes have T g s below −60 °C, T d s up to 230 °C, and Young's modulus up to 4.2 MPa. The overall combined reaction kinetics were studied by DSC yielding an activation energy of 76 kJ/mol by the Kissinger method. These ion conducting membranes have conductivities up to 10 −6  S/cm at 30 °C under anhydrous conditions. They have potential to be used in CO2 separation applications as they exhibit CO2 permeability of 59–110 Barrer and CO2 /N2 selectivity of 25–48.